PENGARUH KOMUNIKASI TERAPEUTIK TERHADAP INTENSITAS NYERI PERSALINAN KALA I DI RUMAH SAKIT Dr. R HARDJANTO BALIKPAPAN TAHUN 2020 - Eli Rahmawati; Sriyayi Sriyayi (Husada Mahakam, 2020)
Background: The first stage of childbirth consists of contractions which can press on the nerve endings, causing pain stimulation. Approximately 90% of deliveries are accompanied by pain and 7-14% are not. Therapeutic communication can reduce the thought of anxiety on the patient, reducing the patient doubts therefor providing stimulation of calm and reducing pain. Objective : To determine the effect of therapeutic communication on the intensity of latent phase I labor pain. Methods: quasi experiment method and one group pretest - posttest research design. The population of all mothers giving birth from January to September was 1,123 people. The sample of this research was 12 latent phase I stage mothers with purposive sampling technique as many as 12 people. Observational research instrument. The data analysis technique is univariate analysis with the mean, median, standard deviation, minimum and maximum mean values, while the bivariate analysis uses paired t test. Result: pre-experimental labor pain average of 6.33, post-experimental average of 3.92. There is an effect of therapeutic communication on the intensity of labor pain during the latent phase of the p value of 0.000. Conclusion:Therapeutic communication affects labor pain. Suggestions for dr. R. Hardjanto Hospital Balikpapan, thereputic communication can be recommended in midwifery care for delivery and to make therapeutic communication SOPs. Keywords: Therapeutic Communication, Labor Pain Intensity